(3JQGLe GdCYdGe GdePchQjf aj cJGH LGeY GdBegGJs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3hHYO agPg ChQGb JJVef PcQ TF eeGJjSQ GdGWdGY Ydjg ef ehGdjO GdBSeGA GdCYdGe GdePchQjf ai eNJUQ GdaQhYi ddEeGe GHf GdMGLH s
(3LGA HBNQgG Gf GdCeGdcgG ehdS GHf YKeGf GHf YHO GdQMef GdCNejfi GdeGdcis
(3LGeY GdGegGJ gh fNJUQ Gdabg ddEeGe CHj YeQh Hf GdMGLHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B102 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs